Teacher training in public policy: the field of professional practice as an opportunity - Di franco, María Graciela; Di franco, Norma Beatriz; Siderac, Silvia (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article proposes an analysis of teacher education programs under the public policy framework put forward in Argentina since the nineties, in two coexistent subsystems: teacher training in Teacher Education Institutes, and teacher training in Public Universities. The first and second sections analyze the context and prevailing legislation which have determined the changes in recent decades. The third section focuses the analysis on a novel curriculum design prescribed for teacher education programs in the whole country - as state policy - in which practice is valued as a field to generate and discuss knowledge. In this context, this document assesses an experience at the university level, carried out in the Human Science Faculty of UNLPam, Argentina, space where research on the institutional curriculum is being conducted, coordinated by the authors of this paper.